Development of Electronic Modules Based on Blended Learning Flipped Classroom in Arabic Language Subject Class X Nuraida Islamic Boarding School Bogor - Penta Eka Nova Rinda; Nurdin Ibrahim; Masitowati Gatot (CV Media Inti Teknologi, 2024)
Learning outcomes in Arabic language subjects in secondary schools are still low, so effective teaching materials are needed to improve Arabic language learning outcomes. The study aims to develop and test the feasibility and effectiveness of developing electronic modules based on blended learning flipped classroom in class X Arabic subjects at Nuraida Islamic Boarding School Bogor. The study uses a development model Borg and Gall which is integrated with the Rowntree model. To test the feasibility of the researcher using validation from media experts, design experts and material experts and also considering the results of user responses from teachers and students. From the results of the feasibility test carried out by material experts at 81.33%, instructional design/media experts at 90%, teacher users at 90% and student users at 95%. Overall, the category was